KEPATUHAN KONSUMSI TABLET TAMBAH DARAH SEBAGAI PENENTU KEJADIAN ANEMIA PADA IBU HAMIL DI DESA SITIARJO KABUPATEN MALANG - Kristinawati, Yesi; Safitri, Rani (ASSYIFA : Jurnal Ilmu Kesehatan, 2026)
Iron deficiency anemia in pregnant women remains a global public health concern, with adherence to iron supplementation continuing to be suboptimal. Objective: To examine the correlation between adherence to iron tablet consumption and the occurrence of anemia among pregnant women in Sitiajo Village, Malang. Quantitative research with a cross-sectional design on 31 pregnant women in their third trimester using purposive sampling. Adherence was assessed using a Guttman scale questionnaire, while anemia status was determined through hemoglobin measurement. Data were analyzed using the Spearman rank correlation test. The study found that 54.8% of respondents were non-adherent to iron tablet consumption, and 51.6% were diagnosed with anemia (Hb < 11 g/dL). A significant correlation was identified between adherence and hemoglobin levels (p-value = 0.001 < 0.05), with a moderate correlation strength (r = 0.548). There is a significant moderate correlation between adherence to iron tablet use and the incidence of anemia in pregnant women. Non-adherence substantially increases the risk of anemia during pregnancy.